The Impact of Minority Shareholder Watchdog Group Activism on the Targeted Firms’ Performance in Malaysia - Rashid Ameer; Rashidah Abdul Rahman (Asian Academy of Management Journal of Accounting and Finance, 2009)
This paper investigates the impact of the Minority Shareholder Watchdog Group (MSWG) activism on the performance of target firms in Malaysia. We find that MSWG-targeted firms earn statistically significantly higher stock returns than non-targeted firms in the long run. The results of various hypothesis tests involving firm performance measures show that MSWG-targeted firms experience significant increases in earnings as compared to non-targeted firms in the first and second years after MSWG involvement. Our results imply that although the MSWG's approach to activism might not be comparable to the initiatives of independent activists in developed financial markets, this type of activism does make a difference by providing minority shareholders and institutional investors with resourceful solutions to reduce information asymmetries that have significant economic consequences.